NATIONAL ECONOMY 2008: A LOOK FROM THE PERSPECTIVE OF THE LINKAGES FOR EMPLOYMENT MATRIX SIZE 111 * 111 - Domínguez, Andrea King; Márquez, Juan Carlos Parra; Arriagada, Osvaldo Pino (European Scientific Journal, ESJ, 2012)
The main purpose of this article is to evaluate the job requirements in each economic activity, starting from an employment matrix, where its coefficients represent job demand for the industry identified as “i” for each job in the industry identified as “j” for producing in the industry j. By using 111 different economic activity sectors, the authors hope to identify those sectors with a bigger chain reaction in terms of job creation.